Gender differences in symptomatology, socio-demographic information and quality of life in Spanish population with long COVID condition: a cross-sectional study - Marcilla-Toribio, Irene; Moratalla-Cebrián, Maria Leopolda; Notario-Pacheco, Blanca; Escudero-Lopez, Miguel Angel; Morales-Cuenca, Nagore; Martinez-Andres, Maria (Frontiers in Public Health, 2024)
Introduction Long COVID patients experience a decrease in their quality of life due to the symptomatology produced by the disease. It is also important to understand how long COVID affects both men and women. The objective of this study is to examine the impact of long COVID symptomatology on the quality of life of Spanish adults from a gender perspective. Methods An observational and cross-sectional study was carried out. Participants were able to complete an online questionnaire using an online platform. A sample of 206 people participated in the study. Results The 80.6% of the sample were women with a mean age of 46.51 (±8.28) and the 19.4% were men with a mean age of 48.03 (±9.50). The medium score in the PAC19-QoL test was 141.47 (±24.96) and segmented by gender, 141.65 (±23.95) for women and 140.82 (±28.66) for men. The most common symptoms in women were muscle and joint pain (94.6%), fatigue (94.0%), discomfort (92.2%), difficulty concentrating (91.0%), and memory loss (88.6%). For men the symptoms included muscle and joint pain (97.5%) and fatigue (97.5%) both occupying first position, discomfort (92.0%), difficulty concentrating (90.0%), mood disturbances (90.0%), and memory loss (87.5%). The chi-square test showed statistical significance (p < 0.005) for socio-demographic information, quality of life scores, and long COVID symptoms by intensities. Conclusion This study shows that there are gender differences in the way that long COVID is experienced.